Research on innovative marketing strategies for small and medium-sized enterprises in the new era - Yanpeng Yao (2024)
With the continuous development of the market economy, small and medium-sized enterprises are facing more and more intense competition, in order to occupy a favourable position in the fierce competition in the market, enterprises must continue to breakthrough and innovation, the innovation of marketing strategy is imperative. Marketing strategy innovation allows enterprises to better focus on customer needs, analyse their own strengths and weaknesses, as well as market positioning and selection of target markets, so as to effectively influence or guide the customer's purchasing decisions. The background, purpose, and significance of marketing strategy innovation research for SMEs are described in this study. The existing literature is sorted out and summarised, and the specific ideas of analysing the problem - solving the problem - and improving the innovation are proposed. This paper combines theory with practice to analyse the existing marketing strategies of SMEs that have changed from the traditional 4Ps to 10Ps (1. Probing 2. Partitioning 3. Positioning 4. Product 5. Price 6. Palace 7. Promotion 8. Personal 9. Political power 10. Public relationship) are analysed in depth. Immediately following the use of SWOT analysis on the existing marketing strategy of small and medium-sized enterprises macro-analysis of the existing marketing strategy of the exposure of the problems of the existing marketing strategy, targeted at the small and medium-sized enterprises marketing strategy innovation ideas. In addition, the three dimensions of ESG practice are used to assess the sustainability of business operations and the impact on social values. Finally, it is proposed that SMEs in this era should adopt what innovative marketing to face the complex and changing society, so as to enhance the core value of their own enterprises, so as to be invincible in the changing times.